2010
DOI: 10.1111/j.1600-0706.2009.18569.x
|View full text |Cite
|
Sign up to set email alerts
|

Sex in a material world: why the study of sexual reproduction and sex-specific traits should become more nutritionally-explicit

Abstract: International audienceRecent advances in nutritional ecology, particularly arising from Ecological stoichiometry and the Geometric framework for nutrition, have resulted in greater theoretical coherence and increasingly incisive empirical methodologies that in combination allow for the consideration of nutrient-related processes at many levels of biological complexity. However, these advances have not been consistently integrated into the study of sexual differences in reproductive investment, despite contempo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(88 citation statements)
references
References 102 publications
(133 reference statements)
3
85
0
Order By: Relevance
“…Veldboom and Haro (2011) found 2 populations of Brachycentrus in which male pupae were more enriched in P than female pupae, and 2 populations where the %P was equal between pupae of both sexes. Morehouse et al (2010) suggested that sexual differences in nutrient content should be expected based on difference in biochemical demand and composition of gametes and other sexually specific structures.…”
Section: Sexual Differences In Nutrient Contentmentioning
confidence: 99%
“…Veldboom and Haro (2011) found 2 populations of Brachycentrus in which male pupae were more enriched in P than female pupae, and 2 populations where the %P was equal between pupae of both sexes. Morehouse et al (2010) suggested that sexual differences in nutrient content should be expected based on difference in biochemical demand and composition of gametes and other sexually specific structures.…”
Section: Sexual Differences In Nutrient Contentmentioning
confidence: 99%
“…Two main frameworks-the Geometric Framework of Nutrition (Raubenheimer et al, 2009;Simpson and Raubenheimer, 2012), which focuses on biochemicals (mainly protein, carbohydrates and lipids), and Ecological Stoichiometry (Sterner and Elser, 2002), which focuses on ratios of elements (mainly carbon, nitrogen and phosphorus)-have been developed to explore the interactive effects of multiple dietary components on organism performance. Some areas of emphasis in this research are that (1) dietary nutritional imbalances provide distinct challenges for organisms depending on the nature of the imbalance (Kay et al, 2005) (2) scarcities of particular nutrients can affect trait expression in specific ways (Morehouse et al, 2010) and (3), the relative availability of nutrients can influence the nature and dynamics of competitive and other species interactions (Moe, 2005).…”
Section: A Disadvantage Of Polyploidy?mentioning
confidence: 99%
“…Adult feeding can have important effects on sexspecific mortality rates and sexual behaviour (see also [55]). For example, Pararge aegeria (Satyridae) adults lived longer when fed [56] and in Pseudoplusia includens (Noctuidae), a shortage of food and water led to sex-specific lifespan in a population in which males normally live as long as females [57].…”
Section: Other Factors Influencing Sex-specific Lifespanmentioning
confidence: 99%